2014
DOI: 10.1111/bju.12764
|View full text |Cite
|
Sign up to set email alerts
|

Uro‐oncology multidisciplinary meetings at an Australian tertiary referral centre – impact on clinical decision‐making and implications for patient inclusion

Abstract: ObjectivesTo analyse the impact of the uro-oncology multidisciplinary meeting (MDM) at an Australian tertiary centre on patient management decisions, and to develop criteria for patient inclusion in MDMs. MethodsOver a 3-month period, all cases presented at our weekly uro-oncology MDM were prospectively assessed, by asking the presenting clinician to state their provisional management plans and comparing this with the subsequent consensus decision. The impact of the MDM was graded as high if there was a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 9 publications
(20 reference statements)
4
85
1
Order By: Relevance
“…However, nearly one-third believed the urological surgeon is best placed suggesting there may be some inconsistency in engagement with a multidisciplinary approach to cancer care despite evidence that it leads to improved survival, adherence to guidelines [45], reduced time to diagnosis and treatment and increased enrolment in clinical trials, in addition to improved patient satisfaction [46]. A recent single-centre Australian study [47] found that discussion of patients at a uro-oncology multidisciplinary meeting resulted in substantial changes to the clinician's original treatment plan in more that one quarter of cases presented. That study additionally reported that where there was no original plan, multidisciplinary discussion increased cross-referral between clinical disciplines, a significant finding given that only one per cent of urologists in our survey sample agreed a radiation oncologist is best placed to decide upon the most appropriate post-operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, nearly one-third believed the urological surgeon is best placed suggesting there may be some inconsistency in engagement with a multidisciplinary approach to cancer care despite evidence that it leads to improved survival, adherence to guidelines [45], reduced time to diagnosis and treatment and increased enrolment in clinical trials, in addition to improved patient satisfaction [46]. A recent single-centre Australian study [47] found that discussion of patients at a uro-oncology multidisciplinary meeting resulted in substantial changes to the clinician's original treatment plan in more that one quarter of cases presented. That study additionally reported that where there was no original plan, multidisciplinary discussion increased cross-referral between clinical disciplines, a significant finding given that only one per cent of urologists in our survey sample agreed a radiation oncologist is best placed to decide upon the most appropriate post-operative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It stipulates that each jurisdiction be responsible for the ethical management and governance of their local registry database. Governance structures were developed in accordance with the Operating Principles and Technical Standards for Australian Clinical Quality Registries as detailed previously [19], and include guidelines on data handling, storage, and access.…”
Section: Governancementioning
confidence: 99%
“…The group comprised of radiation oncologists, urologists, epidemiologists, and research scientists; four members being Directors of cancer registries. The group was provided with a comprehensive list of data items collected by each State/Territory cancer registry [20], and by prostate cancer-specific registries in South Australia [21], Victoria [19] and United States [22]. Feasibility and utility of collecting each of the data items at a population level was considered in developing the minimum data list for collection by the PCOR-ANZ.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is discrepancy in the literature about the effectiveness of MTBs in the field of urology. One study reports only 1.6% of genitourinary tract (GU) cancer patients experienced a change in their treatment decision following MTB discussion 10 , while others report rates as high as 26.7-32.3% 3,11 . As such, current NCCN guidelines limit recommendations to only select GU oncology patients 2 .…”
Section: Introductionmentioning
confidence: 99%